2009
DOI: 10.1016/j.placenta.2009.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Growth Restriction is Associated with Accelerated Telomere Shortening and Increased Expression of Cell Senescence Markers in the Placenta

Abstract: A hallmark of fetal growth restriction (FGR) is restricted placental development and insufficient nutrient supply to the fetus. It has previously been shown that activity levels of telomerase, the enzyme responsible for completing replication of telomeric DNA during cell division, is suppressed in FGR placenta samples as compared to control placenta samples from donors of the same gestational age. Here we examine whether telomere length maintenance is also compromised in FGR placenta samples. Southern analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 18 publications
7
75
1
Order By: Relevance
“…This relationship between low birth weight and shorter TL has been found previously in placenta samples (Davy et al, 2009) but was not found in a small study measuring TL in cord blood (Akkad et al, 2006) nor in three cohorts (including 124 MZ and DZ twin pairs) from Finland (Kajantie et al, 2012). These negative reports do not necessarily contradict our findings.…”
Section: Discussionsupporting
confidence: 73%
“…This relationship between low birth weight and shorter TL has been found previously in placenta samples (Davy et al, 2009) but was not found in a small study measuring TL in cord blood (Akkad et al, 2006) nor in three cohorts (including 124 MZ and DZ twin pairs) from Finland (Kajantie et al, 2012). These negative reports do not necessarily contradict our findings.…”
Section: Discussionsupporting
confidence: 73%
“…41 Also, the expression of telomere-induced senescence markers p21 and p16 is elevated, and anti-apoptotic protein Bcl-2 is decreased in IUGR placentas. 88 Together with increased OS markers and reduced antioxidants capacity, the evidence of ageing markers supports the concept of the role of OS in placental ageing and IUGR.…”
mentioning
confidence: 59%
“…The placenta is an organ that may be related to several diseases: preeclampsia (PE), HELLP syndrome (hemolysis, elevated liver enzymes, low platelet count), gestational hypertension (GH), intrauterine growth restriction (IUGR), and small for gestational age (SGA) fetus. In addition, recent studies suggest that cell senescence may play a role in PE and IUGR (Biron-Shental et al 2010;Kudo et al 2000;Izutsu et al 1998;Davy et al 2009). …”
Section: Introductionmentioning
confidence: 99%